Augmenting nursing care quality and implementing change management in India: an amalgamated approach. (25th April 2013) - Rinkoo, Arvind Vashishta; Singh, Garima; Kaur, Ramanjeet; Chandra, Vidha; Masih, Leela; Chandra, Hem
<x xml:space="preserve">Abstract</x> Background and aim High dependency on nursing care in healthcare delivery systems in recent times has made the quality appraisal of nursing care even more imperative for nursing administrators. This study demonstrates the utility of a two‐phase technique to identify the most significant shortcomings pertaining to nursing care delivery in general wards of a tertiary care hospital. The same could be used to set priorities. Methods The first phase involved the use of the Delphi technique facilitating the experts to identify the major problems. The mean rank score was used for grading the problems. The second phase of the study involved getting direct feedback from the ward nurses. The sample size was 147 at a level of significance of 5%. Results Consensus was reached among experts on four problems that should galvanize nursing administration vis‐à‐vis quality improvement. The responses of ward nurses in the second phase gave a better insight into these problems. Conclusion and implications for nursing management Identifying the existing problems and fostering a team spirit among all stakeholders hold the key in strategizing quality improvement in nursing care. Nursing administrators worldwide, after making suitable situation‐specific customizations, may use this approach to realize both these objectives.